Odpowiedź :
[tex]2\frac{9}{16}-1=\boxed{1\frac{9}{16}}\\\\12\frac{2\cdot4}{3\cdot4}+1\frac{3\cdot3}{4\cdot3}=12\frac{8}{12}+1\frac{9}{12}=\boxed{14\frac{5}{12}}\\\\8\frac{1\cdot3}{8\cdot3}-2\frac{2\cdot8}{3\cdot8}=8\frac{3}{24}-2\frac{16}{24}=\boxed{5\frac{11}{24}}[/tex]
Cześć!
[tex]2\frac{9}{16} - 1 = 1\frac{9}{16} \\\\12\frac{2}{3} + 1 \frac{3}{4} = 12 \frac{8}{12} + 1\frac{9}{12} = 13 \frac{17}{12} = 14 \frac{5}{12} \\\\8\frac{1}{8} - \frac{2}{3} = 8 \frac{3}{24} - \frac{16}{24} = 7 \frac{27}{24} - \frac{16}{24} = 7\frac{11}{24}[/tex]
Pozdrawiam :)